Archaeology and biblical interpretation - Bartlett, John R. (John Raymond) (Routledge, 1997)
The contributors in this book use the most recent research in key areas - the early settlements of Israel, early Israelite religion, Qumran, Jerusalem, early Christian churches - to show that ancient writings and modern archaeology can illuminate each other, but only when used with professional care. The essays represent a new generation of archaeologists and historians, with new social, political and religious concerns who draw a fresh and vital picture of the emergence of ancient Israel.